2020
DOI: 10.1108/jhom-06-2019-0167
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing implementation of organizational health literacy: a realist review

Abstract: PurposeHealthcare systems are increasing in complexity, and to ensure people can use the system effectively, health organizations are increasingly interested in how to take an organizational health literacy (OHL) approach. OHL is a relatively new concept, and there is little evidence about how to successfully implement organizational health literacy interventions and frameworks. This study, a literature review, aims to explore the operationalization of OHL.Design/methodology/approachA realist literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
1
18
0
2
Order By: Relevance
“…(3) intermediate organizational outcomes showed evidence of embedding of OHL into policies and structures, staff training, and interventions to improve screening, communication and patient engagement [25][26][27][30][31][32][33]41,42]. This review thus indicates a growing awareness of how to achieve sustainable improvement on various OHL-domains, and supports the findings in recent reviews by Zanobini et al (2020) [18] and Meggetto et al (2020) [51].…”
Section: Discussionsupporting
confidence: 76%
“…(3) intermediate organizational outcomes showed evidence of embedding of OHL into policies and structures, staff training, and interventions to improve screening, communication and patient engagement [25][26][27][30][31][32][33]41,42]. This review thus indicates a growing awareness of how to achieve sustainable improvement on various OHL-domains, and supports the findings in recent reviews by Zanobini et al (2020) [18] and Meggetto et al (2020) [51].…”
Section: Discussionsupporting
confidence: 76%
“…Meggetto et al [ 34 ] identified 19 different terms to describe OHL, the three most frequent terms being health system health literacy , organizational health literacy , and health literacy practice/s . They observed that different terms overlap in content, but aim at different levels or contexts and concluded an interdependence between the terms and concepts: “Within health system health literacy sits OHL, and within this sits health literacy practice” [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comprehensive and current information on the criteria’s underlying concepts and terminologies, and on the instruments to measure these criteria, is expandable. Only a few studies investigated theories and concepts [ 30 ] and terminologies [ 34 ] of OHL. Both studies did not relate to the variety of criteria that characterize HLHCOs.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the scientific discussion on the relevance of the environment has gained momentum (35)(36)(37). For instance, the research activities have yielded the construct of organizational health literacy as a beneficial characteristic of institutions or systems supporting people to navigate, understand, and use information and services to take care of their health (34,38,39). The considerations of the environment also permeated the action plans of several countries (40), which provide national efforts with an adequate framework for health promotion.…”
Section: The Role Of the Environment In Health Literacy Researchmentioning
confidence: 99%